Perilaku Masyarakat Baduy dalam Mengelola Hutan, Lahan, dan Lingkungan di Banten Selatan - Gunggung Senoaji (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2011)
Baduy community is a Sundanese ethnic isolating themselves around Kendeng Mountains, South Banten. They occupy an area about 5101.8 hectares of land in which the property rights were granted from the government. The people strictly adhere to their customary rules and norms. Hence, this article described to conditions of Baduy community and their behaviour in managing its forests, land and environments. The Baduy behaviour is different from the general community. These behaviour were believed to be initiated by the decrease availability of cultivated areas due to the population growth and influence their customary rules and norms. Their behaviour forms of local wisdom in managing the environment. The behaviour of Baduy community implemented in managing agricultural land, forest, and environment.